2003
DOI: 10.1007/978-3-540-40035-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase-based therapeutics: lessons from PTP1B

Abstract: The family of Protein Tyrosine Phosphatases (PTPs), which is encoded by ~100 genes in humans, plays a critical role in the regulation of signal transduction. Recently a variety of links between aberrant PTP function and human disease have been defined and it has become apparent that generation of PTP inhibitors may present novel avenues for therapeutic intervention in several, major human diseases. The most clearly defined example is the potential of PTP1B as a target for treatment of diabetes and obesity. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…With the validation of PTP1B as a therapeutic target for the treatment of diabetes and obesity, interest has grown in exploiting the PTPs for development of small‐molecule drugs . Nevertheless, the reactivity of the essential active‐site cysteine has posed a significant challenge to the generation of reversible active‐site‐directed inhibitors . In the many high throughput screens of small‐molecule libraries that have been conducted to date in industry and academia, it has become apparent that the presence of this potent nucleophile at the catalytic center renders the PTPs sensitive to the effects of Michael acceptors, leading to irreversible inhibition of PTP function.…”
Section: Discussionmentioning
confidence: 99%
“…With the validation of PTP1B as a therapeutic target for the treatment of diabetes and obesity, interest has grown in exploiting the PTPs for development of small‐molecule drugs . Nevertheless, the reactivity of the essential active‐site cysteine has posed a significant challenge to the generation of reversible active‐site‐directed inhibitors . In the many high throughput screens of small‐molecule libraries that have been conducted to date in industry and academia, it has become apparent that the presence of this potent nucleophile at the catalytic center renders the PTPs sensitive to the effects of Michael acceptors, leading to irreversible inhibition of PTP function.…”
Section: Discussionmentioning
confidence: 99%
“…Most prominent among these is PTP1B, which has been implicated in the downregulation of insulin signaling by a variety of approaches, including the phenotype of the PTP1B knock-out mouse (44,45). This and the identification of this phosphatase as a regulator of signaling in response to cytokines such as leptin (46 -48) have led to considerable attention being focused on PTP1B as a target for development of novel therapeutics for treatment of both diabetes and obesity (49,50). In our analysis, we observed that insulin stimulation induced the rapid and transient oxidation and inactivation of PTP1B.…”
Section: Discussionmentioning
confidence: 99%
“…These endeavors have been strongly supported by the availability of an impressive number of x-ray structures (reviewed in Ref. 56). Furthermore, the seminal publications that demonstrated that PTP1B is a key negative regulator of insulin and leptin signaling (6 -9) provided the first evidence that PTPs indeed could be attractive molecular targets.…”
Section: Discussionmentioning
confidence: 99%